2020
DOI: 10.21203/rs.3.rs-53476/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Has Bipolar Disorder become a predominantly female gender related condition? Analysis of recently published large sample studies

Abstract: Bipolar Disorders are disabling and severe psychiatric disorders, commonly perceived as equally affecting both men and women. The prevalence of BD in the general population has been growing over the last decade, however, few epidemiological studies are available regarding BD gender distribution, leaving unanswered the question whether the often reported increment of BD diagnosis could be gender specific. In fact, BD in female patients can often be misdiagnosed as MDD, leaving such women non correctly treated f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Studies that have found a more pronounced effect of mothers psychopathology on the offspring's mental health could be of relevance. 34 Another potential explanation could be gender differences in number of suicide attempts prior to suicide 35 or gender differences in mental disorders such as bipolar disorder 36 that is especially stressful to cope with for the relatives. Unfortunately, we did not have access to diagnostic data allowing us to further explore these hypotheses.…”
Section: Discussion Employment At Time Of Bereavementmentioning
confidence: 99%
“…Studies that have found a more pronounced effect of mothers psychopathology on the offspring's mental health could be of relevance. 34 Another potential explanation could be gender differences in number of suicide attempts prior to suicide 35 or gender differences in mental disorders such as bipolar disorder 36 that is especially stressful to cope with for the relatives. Unfortunately, we did not have access to diagnostic data allowing us to further explore these hypotheses.…”
Section: Discussion Employment At Time Of Bereavementmentioning
confidence: 99%